The Impact of Quality of Work Life and Job Satisfaction on Employee Performance of PT. Madubaru PG-PS Madukismo - Nurma Asri Asharini; Suhatmini Hardyastuti; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
This study aimed to (1) determine the effect of the quality of work life (QWL) and job satisfaction to organizational commitment ; (2) finding out the effect of the QWL, job satisfaction, organization commitment to employee performance ; (3) finding out the effect of the QWL and job satisfaction to employee performance with organization commitment as intervening variable. The sample in this research was employees of PT. Madubaru PG-PS Madukismo in Yogyakarta using 100 respondents; the sampling technique was using simple random sampling technique. The types of data used were primary and secondary data with data collecting techniques of survey approach (questionnaire). The data analysis technique used was Structural Equation Modeling (SEM) through AMOS 21 program and SPSS 23. The result of the research is that QWL does not affect the organizational commitment while job satisfaction affects the organizational commitment. The QWL and job satisfaction do not affect employees’ performance, while organizational commitment affects the employees’ performance. The QWL does not affect the employees’ performance indirectly. Job satisfaction affects employees’ performance indirectly with organizational commitment as intervening variable. The company should further enhance the employees’ organizational commitment in order to higher the employees’ performance.